Effectiveness of Low-Impact Aerobic Exercise to Improve Cardiorespiratory Fitness and Quality of Life in Elderly - Setiawan, Cahyo; Ramadhani, Alinda Nur; Rahayu, Umi Budi (Althea Medical Journal, 2025)
Background: Aging is associated with declining physical health and decreased quality of life in the elderly population. In response to the rising challenges faced by the aging demographic, this study aimed to investigate the effects of low-impact aerobic exercise on cardiorespiratory fitness and overall quality of life in the elderly. Methods: A quasi-experimental study design was employed involving 42 elderly participants who underwent a three-month low-impact aerobic exercise intervention. This study was conducted in the work area of the Surakarta City Health Service from June to August 2023. Cardiorespiratory fitness was measured using the Harvard Step Test, and quality of life was assessed through the World Health Organization Quality of Life Brief Version (WHOQOL-BREF) questionnaire. The effect of low-impact aerobic exercise on cardiorespiratory fitness and quality of life was analyzed using the non-parametric test Wilcoxon Test.Results: Most respondents were aged 60–65 years (66.7%) and female (71.5%). The study revealed a significant improvement in both cardiorespiratory fitness (p=0.025) and quality of life (p<0.000) among the elderly participants after low-impact aerobic exercise intervention.Conclusion: Low-impact aerobic exercise has an effect on increasing cardiorespiratory fitness and  quality of life in the elderly. This finding is expected to be one of the main therapies that can help maintain the health and well-being of the geriatric population.